A STRATEGIC MANAGEMENT APPROACH TO STABILIZING RISK, GOVERNANCE, EARNINGS, AND CAPITAL UNDER A NEW VISION OF PT. BANK MUAMALAT INDONESIA - Sazly, Syukron; Haryadi, Budhi; Siregar, Otto; Siswantoro, Yuni (Univesitas Muhammadiyah Tangerang, 2025)
This study aims to analyze the strategic management approach of PT. Bank Muamalat Indonesia, Tbk in improving financial health and realizing the new vision established in 2025. The method used is qualitative descriptive with secondary data analysis from financial reports, OJK publications, and other relevant documents. The result shows, the bank faced significant challenges in the initial years following the new vision’s launch, particularly in the indicators of NPF (2.34%), BOPO (105%), and ROA (0.3%), although CAR (15%) and FDR (82%) remained relatively strong. Strategic management was applied through strengthening risk management, operational efficiency via digitalization, sharia product innovation, and internalization of blessing values as part of the organizational culture. The study’s limitations include a greater focus on quantitative data than qualitative data and a case study limited to a single institution, requiring caution in drawing conclusions. Future research is recommended to use mixed methods and compare practices with other sharia banks so that, evaluation and benchmarking is believed to enhance Bank Muamalat’s competitiveness and sustainability.